The transmittable through stinging microbiota differs between honeybees and wasps: a potentially greater microbial risk of the wasp sting for humans - Gkitsaki, Ioanna; Papachristoforou, Alexandros; Michailidou, Sofia; Karamvalis, Nikolaos; Iliadis, Ioannis; Graikini, Dimitra; Sakarikou, Christina; Tsoukis, Evangelos; Argyriou, Anagnostis; Giaouris, Efstathios (My University, 2023)
The authors regret that an unnecessary sentence* was embedded at the beginning of the “Results and discussion” section. * “We refer to 3 different parameters: (i) microbial ecology of the environment. (ii) nutritional habits. (iii) social habits” The original article has been corrected. The authors apologize for any inconvenience caused.
Keywords: Bacterial pathogens; Honeybees; Hymenoptera stinging; Infection; Microbiota; Wasps